EFFECTIVENESS E-HEALTH TO SELF MANAGEMENT OF DIABETES MELLITUS TYPE 2 : LITERATURE REVIEW - Siti Hardiyanti; Firnanda Erindia; Sigit Mulyono; Achsan Tudhonny; Umdatus Soleha (Universitas Airlangga, 2022)
Introduction: Patient and nurse is constructive relationship beneficial in a self-management support approach. Research shows e-health intervention has the potential to support self-management for adults with type 2 diabetes. The purpose this article to apply the application of e-health to people with type 2 diabetes mellitus. Method: Method is search journal articles through basic data in ProQuest, Clinical key, EBSCO with a time span of 2018-2022, using the keywords